(untitled) (Journal of Student Affairs in Africa, 2021)
This article reports on a qualitative study that evaluated first-year students’ lived experiences of attending a 12-week student support programme focused on fostering mindsets. Participants included 545 first year Engineering students enrolled for academic studies at a South African university. All participants completed qualitative narrative sketches depicting their experiences. A random sample of 300 students’ narrative sketches was included as data in the qualitative study. The data were analysed using thematic analysis, and Dweck’s theory on mindsets served as the theoretical lens through which the data were interpreted. The results indicate that the majority of students experienced significant personal growth from attending the student support programme. Additionally, the findings point to the relevance and importance of offering student support programmes focused on exploring mindsets to first-year students. The results of this exploratory study suggest that mindset theory should be considered as an essential component when advising first-year South African Engineering students. Furthermore, we make a case for the relevance of positive psychology-based development programmes for first-year students.